21.6k views
5 votes
Multi step equations

Multi step equations-example-1
User KarateJB
by
5.6k points

2 Answers

5 votes

Answer:

Explanation:

First you distribute( multiply) the -6 to everything inside the parentheses.

Now you have -86= 18p + 18 - 5p

Now combine like terms

-86 = 13p + 18

Now subtract 18 from both sides of the equal sign

-104 = 13p

Now divide by 13 on both sides of the equal sign.

p = -8

User Prmths
by
5.4k points
2 votes

-86 = -6(-3p - 3) - 5p

Distribute the -6 into the parentheses:

-86 = (-6 * -3p) + (-6 * -3) - 5p

-86 = 18p + 18 - 5p

Simplify:

-86 = 13p + 18

Subtract both sides by 18:

-86 - 18 = 13p + 18 - 18

-104 = 13p

Divide both sides by 13:


(13p)/(13) =
(-104)/(13)


(p)/(1) =
(-8)/(1)

p = -8

Good luck! If you have any questions, don't be afraid to ask :))

-T.B.

User Cfl
by
6.3k points